Facultative grazing and bioturbation by macrodetritivores alter saltmarsh plant–plant interactions under stress. (12th May 2016) - Howison, Ruth A.; Olff, Han; van Puijenbroek, Marinka E. B.; Smit, Christian
Summary: The importance of positive plant– plant interactions is generally suggested to increase towards more stressful conditions, due to mutual stress amelioration between plants. Bioturbating macrodetritivores can also ameliorate stress through bioturbation, but can also become selective herbivores under food‐limited conditions, making the outcome of plant– plant interactions under stress in the presence of macrodetritivores unclear. We studied how combining environmental stress (waterlogging) with the presence of the soil macrodetritivore Orchestia gammarellus affected the outcome of the interaction between two salt marsh plants: the tall, late successional Elytrigia atherica and the shorter, early successional Festuca rubra . In a replacement design competition experiment under controlled conditions, we found that soil redox potential was negatively affected by waterlogging and positively affected by the presence of O. gammarellus . The survival and shoot biomass of E. atherica was not significantly affected by waterlogging or by the presence of bioturbators. The survival and shoot biomass of F. rubra was especially decreased when waterlogging was combined with the presence of O. gammarellus, as this macrodetritivore turned into a selective grazer on F. rubra under these conditions. We found that E. atherica produced double shoot biomass and F. rubra produced much less shoot biomass in their mixed cultures than was expected from the monocultures of same waterlogging/ Orchestia treatments. Hence, the presence of the bioturbator strongly promoted the competitive advantage of E. atherica over F. rubra due to the combination of stress amelioration for the first species and selective herbivory on the second species. Synthesis . This study shows that the inclusion of bioturbating macrodetritivores complicates the standard prediction that plant– plant interactions become more positive towards more stressful conditions. A novel insight is that macrodetritivores can affect the structure and diversity of plant communities through multiple mechanisms. Under benign conditions bioturbating macrodetritivores ameliorated soil conditions, permitting co‐occurrence of competing plant species. At high environmental stress (waterlogging) macrodetritivores selectively graze higher quality plant species and emerging seedlings, thus promoting dominance of the lower quality species. Hence, the facultative feeding behaviour of macrodetritivores deserves further attention. Abstract : Soil macrodetritivores can also be important in ecosystems as stress alleviators, leading to alternative explanations for the outcome of competition between plant species. Using a full factorial experimental approach we disentangle multiple mechanisms through which soil macrodetritivores affect plant interactions, including soil amelioration and facultative grazing under stress (Photo credit: Roy Kleukers).